Influence of the satellite observation matching radius on the ERA5 wave height calibration off the coast of Peru - Guzmán, Emanuel (2025)
This study analyzes how the spatial matching radius used to pair satellite-derived significant wave height observations with ERA5 wave estimates influences calibration performance along the Peruvian coast. To this end, three matching radii—20, 30, and 50  km—were evaluated using linear, exponential, and range-based calibration methods. The results show that the choice of matching radius has a direct and significant impact on calibration quality: smaller radii limit the number of available satellite observations, while larger radii reduce spatial representativeness and increase error. An intermediate radius of 30 km was found to provide the most balanced performance, improving consistency and reducing bias across all calibration approaches. Exponential calibration yielded slightly better improvements in several cases, although all methods performed satisfactorily. Overall, these findings highlight the importance of selecting a matching radius that reflects both regional oceanographic characteristics and data availability—particularly in areas such as the Peruvian coast, where in situ measurements are scarce and satellite observations play a crucial role in coastal wave modeling and operational forecasting.